Effects of Climate Change on Mountain Waters: A Case Study of European Alps - Laghari, A. N.; Walasai, G. D.; Jatoi, A. R.; Bangwar, D. K.; Shaikh, A. H. (Engineering, Technology & Applied Science Research, 2018)
The Alps play a vital role in the water supply of the region through the rivers Danube, Rhine, Po and Rhone while they are crucial to the ecosystem. Over the past two centuries, we witnessed the temperature to increase by +2 degrees, which is approximately three times higher than the global average. Under this study, the Alps are analyzed using regional climatic models for possible projections in order to understand the climatic changes impact on the water cycle, particularly on runoff. The scenario is based on assumptions of future greenhouse gases emissions. The regional model results show the consistent warming trend in the last 30-year span: temperature in winter may increase by 3 to 4.5°C and summers by 4 to 5.5°C. The precipitation regime may also be altered: increasing about 10-50% in winter and decreasing about 30-60% in summer. The changes in the amount of precipitation are not uninformed. Differences are observed particularly between the North West and South East part of the Alps. Due to the projected changes in alpine rainfall and temperature patterns, the seasonality of alpine flow regime will also be altered: massive rise will occur in winter and a significant reduction in summer. The typical low flow period during winter will also be shifted to late summer and autumn.